Avaliação nutricional, desempenho e características morfométricas de cordeiros de diferentes grupos genéticos terminados em sistema de integração lavoura-pecuária com suplementação em região semiárida - Soares, Sérgio Luiz Silva (2018)
This study was carried out to characterise pastures composed by corn, massai grass and blue pea, as well as analyse the performance, ingestive behaviour, microbial protein production and morphometric measurements in vivo of Santa Inês and Somalis Brasileira sheep finished in an integrated crop-livestock system. Twenty-eight animals were used, being 14 Santa Inês and 14 Somalis Brasileira lambs, non-castrated, with initial average weight of 18.43 ± 1.42 kg and, approximately, 120 days old. Also, were determined the chemical-bromatological and botanic composition, structural characteristics, productivity index and kinetic parameters of pasture degradation. The estimation of consumed dry matter was performed and the daily average weight gain, final body weight, indigestive behaviour in pasture and nictemeral, microbial protein production as well as its efficiency and the animals’ morphometric measurements in vivo were measured. The pasture showed contents of 9.44% of crude protein and 67.89% of insoluble fibre in neutral detergent, with total biomass production of 3.747 kg of DM/ha. The dry matter, crude protein and insoluble fibre in neutral detergent of the pasture presented, respectively, partial degradability of 69.7; 63.66 and 67.95% and degradation rate of the potentially degradable insoluble fraction of 4.75; 3.00 and 5.00%/h. The Santa Inês and Somalis Brasileira breeds showed, respectively, daily average weight gain of 166.13 and 149.64 g/day, final body weight of 28.66 and 27.79 kg and estimated average of consumed dry matter of 807.67 and 802.79 g/day, which did not differ statistically (P>0.05). The ingestive behaviour, production and microbial protein efficiency production were similar between the two breeds (P>0.05), while morphometric measurements showed different correlations within productive index to two genotypes, each genetic group being monitored and selected by specific morphometric measurements. Due to a complementarity provided by characteristics of the corn, massai grass and blue pea, the consorted pasture may present high biomass production with favourable nutritional quality, making possible a satisfactory performance of Santa Inês and Somalis Brasileira lambs finished in an integrated crop-livestock system.